2019
DOI: 10.1149/2.0571904jes
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Accelerator Alkyl Chain Length on the Microvia Filling Performance in Copper Superconformal Electroplating

Abstract: In addition to the commercialized accelerator bis-(sodium sulfopropyl)-disulfide (SPS), we designed and synthesized two other disulfide compounds, namely, bis-(sodium sulfohexyl)-disulfide (SHS) and bis-(sodium sulfoethyl)-disulfide (SES), to investigate the effect of their alkyl chain lengths on the microvia filling performance. The galvanostatic measurements show that the addition of Cl − to different accelerator-containing solutions leads to the same synergistic effects at a current density of 20 mA/cm 2 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The electrochemistry of PEG-Cl-SPS has been studied thoroughly [ 5 , 44 , 45 , 46 ]. Unfortunately, there is still a limited number of appropriate experiments oriented toward the combination of cyclic voltammetry experiments with a modern spectroscopic technique that is useful for resolving the interaction of PEG/SPS/Cl.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemistry of PEG-Cl-SPS has been studied thoroughly [ 5 , 44 , 45 , 46 ]. Unfortunately, there is still a limited number of appropriate experiments oriented toward the combination of cyclic voltammetry experiments with a modern spectroscopic technique that is useful for resolving the interaction of PEG/SPS/Cl.…”
Section: Introductionmentioning
confidence: 99%
“…[ 40,41 ] This structure's bending and rotating properties can effectively bring the Cu + in solution closer to the electrode surface for achieving rapid discharge and the accelerated deposition of copper. [ 42 ]…”
Section: Resultsmentioning
confidence: 99%
“…[40,41] This structure's bending and rotating properties can effectively bring the Cu + in solution closer to the electrode surface for achieving rapid discharge and the accelerated deposition of copper. [42] As shown in region-III of Figure 2, the reduction peak potential negatively shifted by about 134 mV after adding HAP compared with VMS curve a, indicating the strong inhibitory effect of HAP. The positive shift of the reduction peak was about 32 and 34 mV after the addition of HP and DPS, respectively.…”
Section: Electrochemical Analysismentioning
confidence: 85%
“…Owing to the uneven local current contribution, the deposition rate of copper at the mouth is generally higher than that at the bottom of the microvia, resulting in quick sealing of the mouth or the formation of voids. To achieve void-free filling, a high concentration of copper ions and kinds of additives (such as a suppressor, accelerator, and leveler) in low concentration (less than 100 mg/L) are needed. It can be easily found that the additives and their concentrations are very hard to regulate due to their different consumption rates and complicated synergistic effects. Besides, the high concentration of sulfuric acid is corrosive to equipment.…”
Section: Introductionmentioning
confidence: 99%